Loucura, a escrita de si no espaço do fora: uma análise de Viagem a Andara, o livro invisível de Vicente Cecim - SALES, Maria Domingas Ferreira de (Universidade Federal do Pará, 2025)
The question of the Amazon as a stronghold for foreign exploration has been a plausible reason for undertaking research in the Humanities area, insofar as it turns to an ethics of social relations. This concern assumes plural dimensions, opening the way for discussions that go beyond the niche of environmental ecology and political geography, becoming a theme of a planetary order. More specifically in the field of literary studies, the relevance of this western concern in the space of poetic saying becomes evident, transposed into different types, modes and discursive genres. And, if sometimes, due to the opacity on the surface of the poetic text, it is imperceptible, this same literary strategy, paradoxically, is what makes this saying possible. Based on this idea, the present thesis is intended to present a reading of the work Viagem a Andara, o livro invisível, by the writer from Pará Vicente Franz Cecim, son of the contemporary Amazon, emphasizing the presence of madness as event of resistance to the explorer/dominator both in the internal context of the fables and in the effect of estrangement aroused by the formal ruptures present in the work. This double deviant outline will allow us to investigate how the power relations between the mad subject and the dominator are constructed and/or how the truths of the text-man are produced. The corpus selected for this approach consists of the seven books that make up the edition published by Editora Iluminuras (1988), titled in the same chronological order in which they appear in this volume: A asa e a serpente, Os animais da terra, Os jardins e a noite, Terra da sombra e do não, Diante de ti só verás o Atlântico, O sereno e As armas submersas. From the comparative reading between the works of the set, it will be possible to perceive both the transversal presence of madness as an explicit theme of the narratives, as well as the transgressive character of the literary process, elaborated from unconventional constructions. These two axes will form the basis for the construction of the third axis whose topics are in line with the defense that the literary work is essentially the space of the outside or the madness of language. This tripod should offer enough elements to answer the fundamental questions of this study: a) How the madness or the madmen mentioned in Cecim's texts - analyzed in the light of Michel Foucault's studies regarding power relations and the historical forms of subjectivation - do they represent modes of resistance to the mechanisms of control and social coercion identified in the Andara set?; b) In what way the practices of repression of the subjects by the domains of the explorer and their developments are supplanted by the deviant character of the events, taken as resistance, both in the time of the fable and in the linguistic-formal construct of the text, revealing themselves as practices of the self or of12 freedom?; Or: c) How do these actions of resistance correspond to the “space of the outside” – thought taken from Blanchot – also conceived in the double face of the poetic text? The results of this academic endeavor led us, therefore, to the defense that madness, as resistance and practices of freedom of subjects in the context of narratives, can also be constituted as a form of subjectivation or writing of the self of the literary making itself - a response motivated by the clamor of the Cecinian text, rebelled and insurgent against the dictates of the civilizing process to which the Amazonian man is submitted.